Tackling transnational crime - McCusker, Rob (Henry Stewart Talks, 2008)
Nature, variety and complexity of cross-border crime, Strategic focus, Types of crime, Types of transnational crime groups, Reducing harm, Reducing operational capacity, scope and effectiveness, Terrorism: convergence and modes of anticipation
Archived at 2022/04/03